Trace elements‐based Auroshell gold@hematite nanostructure: Green synthesis and their hyperthermia therapy - Hadil M. Alahdal; Sumya Ayad Abdullrezzaq; Hawraz Ibrahim M. Amin; Sitah F. Alanazi; Abduladheem Turki Jalil; Mehrdad Khatami; Marwan Mahmood Saleh (IET Nanobiotechnology)
Abstract Hyperthermia is an additional treatment method to radiation therapy/chemotherapy, which increases the survival rate of patients without side effects. Nowadays, Auroshell nanoparticles have attracted much attention due to their precise control over heat use for medical purposes. In this research, iron/gold Auroshell nanoparticles were synthesised using green nanotechnology approach. Auroshell gold@hematite nanoparticles were synthesised and characterised with rosemary extract in one step and the green synthesised nanoparticles were characterised by X‐ray powder diffraction, SEM, high‐resolution transmission electron microscopy, and X‐ray photoelectron spectroscopy analysis. Cytotoxicity of Auroshell iron@gold nanoparticles against normal HUVEC cells and glioblastoma cancer cells was evaluated by 2,5‐diphenyl‐2H‐tetrazolium bromide method, water bath hyperthermia, and combined method of water bath hyperthermia and nano‐therapy. Auroshell gold@hematite nanoparticles with minimal toxicity are safe against normal cells. The gold shell around the magnetic core of magnetite caused the environmental and cellular biocompatibility of these Auroshell nanoparticles. These magnetic nanoparticles with targeted control and transfer to the tumour tissue led to uniform heating of malignant tumours as the most efficient therapeutic agent.